Nucleotide polymorphism of starch synthesis genes in thai rice - Jangsutthivorawat S. (2014)
Starch composition and cooking quality are important rice-grain characteristics of interest to breeders. One hundred and ninety-two accessions of Oryza, mostly from Thailand, were assayed using PCR-SSCP and alleles were identified at seven starch-synthesis gene loci (GBSSI, SSSIIIa, SSSIIIb, SSSIVa, SSSIVb, RBE1 and RBE3). The nucleotide sequences were obtained corresponding to each of the SSCP patterns observed and the sequences were submitted to GenBank (accession numbers EF990806 - EF990893). The frequency of nucleotide polymorphisms at these loci was about 1 SNP per 29 bp. A total of 136 nucleotide polymorphisms (SNPs), 16 insertions/deletions (indels) and 4 SSRs were identified. The SSRs were found at the GBSSI (CT, AATT), SSSIVb (GGGTT) and RBE1 (CT) loci. The nucleotide diversity, as measured by π, ranged from 0.00086 (RBE3) to 0.02747 (SSSIVa) and nucleotide polymorphism, as measured by q, ranged from 0.00154 (RBE3) to 0.02337 (SSSIVa). The Oryza accessions from Thailand in this study displayed a high nucleotide diversity compared with previous estimates of Oryza species based on estimates of multiple loci.